(untitled) (Journal of Universal Science Research, 2024)
This article covers the maashhur gardens of Japan, the peculiarities of their nature, Customs and traditions. It is believed that through the beauty of nature, a person knows himself, and his thinking has a noble effect on the world of the human soul. In the process of building a Japanese garden, according to Oriental legends, many centuries-old trees with living spirit and energy were preserved. Also on the territory of the garden there are sakura trees - decorative cherries, the observation of their flowering is an integral part of Japanese culture.